The Experiences of Minority Doctoral Students at Elite Research Institutions. Issue 163 (13th September 2013) - Graham, Eva
Abstract: Minority doctoral students at elite and highly competitive private research universities encounter distinctive challenges that can impact persistence, time to degree, and professional outcomes.